The Role of Teachers in Teaching Arts, Culture, and Crafts (SBdP) to Grade V Students at SD Negeri 8 Bontoramba - Aderia Latipah; Yun Ratna Lagandesa (MASI Mandiri Edukasi, 2025)
This study aims to examine the role of teachers in implementing Arts, Culture, and Crafts (SBdP) learning for fifth-grade students at SD Negeri 8 Bontoramba. The research addresses the problem of how teachers contribute to planning, implementing, motivating, and evaluating SBdP learning in accordance with educational objectives. This study employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. The results indicate that teachers play a central role in optimising SBdP instruction. As planners, they design teaching modules and select media that not only enhance cognitive skills but also foster creativity, positive attitudes, and an appreciation for art. As facilitators, they apply interactive methods such as demonstrations, discussions, and hands-on practice, while utilising the surrounding environment as a learning resource. As motivators, they foster student confidence and creativity through encouragement and rewards. As evaluators, they conduct comprehensive assessments of knowledge, skills, and attitudes using tests, portfolios, and performance evaluations. Challenges encountered include limited media, varying student abilities, and insufficient facilities for art activities. Despite these constraints, teachers demonstrate adaptability by creatively utilising available resources. These results suggest the need for improved school facilities and continuous teacher training under the Merdeka Curriculum.